If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(2x + -3) = 2(x + -44) Reorder the terms: -4(-3 + 2x) = 2(x + -44) (-3 * -4 + 2x * -4) = 2(x + -44) (12 + -8x) = 2(x + -44) Reorder the terms: 12 + -8x = 2(-44 + x) 12 + -8x = (-44 * 2 + x * 2) 12 + -8x = (-88 + 2x) Solving 12 + -8x = -88 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -8x + -2x = -88 + 2x + -2x Combine like terms: -8x + -2x = -10x 12 + -10x = -88 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + -10x = -88 + 0 12 + -10x = -88 Add '-12' to each side of the equation. 12 + -12 + -10x = -88 + -12 Combine like terms: 12 + -12 = 0 0 + -10x = -88 + -12 -10x = -88 + -12 Combine like terms: -88 + -12 = -100 -10x = -100 Divide each side by '-10'. x = 10 Simplifying x = 10
| w=w+3 | | -9(x+2)=36 | | 124.25=36.75+36.75+x | | 50=10x+5y | | y+11=2y-31 | | 5x^2+(4x+9)=10 | | 15x^2-4x+4= | | 8x-10x+8=-20 | | log[2](10+3x)=5 | | 2+3ln(x-1)=8 | | 34=x+9 | | -2(4x+9)=30 | | 4=12(x)+40 | | 3(a+1)+4(2a-3)= | | 2x^2-9x^2+7x+6=0 | | (6u^2-2u+2)+(-7u^2-3u+5)-(-9u^2+5u-3)= | | 7p-4=29+2p | | 29=14x-8 | | 4(u+2u)=8u+30 | | 12-18=6z | | x^2-2x+2=4 | | 2v+4v=42 | | -24x+36=2x | | g=d+e+f | | 1.2-4.3a-3.1a=-14.34 | | 15.3y=0.08 | | 7y=7y+7 | | (y+11)12= | | -10=-2x+5x-7 | | 1+7n-18=-9 | | 2x-4-5x+6= | | (u+10)12= |